Economic liberalization and the emerging patterns of social inequality in Sri Lanka - Hettige, S.T. (Natural Resources Energy Science Autority of Sri Lanka:Colombo, 1995)
Abstract available from Library, Please quote title when requesting
Keywords: Social structural change; Economics